2022
DOI: 10.1002/jpen.2371
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutrition in critically ill patients under vasoactive drug therapy: The NUTRIVAD study

Abstract: Background Enteral nutrition (EN) in critically ill patients requiring vasoactive drug (VAD) support is controversial. This study assesses the tolerability and safety of EN in such patients. Methods This prospective observational study was conducted in 23 intensive care units (ICUs) over 30 months. Inclusion criteria were a need for VADs and/or mechanic circulatory support (MCS) over a minimum of 48 h, a need for ≥48 h of mechanical ventilation, an estimated life expectancy >72 h, and ≥72 h of ICU stay. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
2
24
0
5
Order By: Relevance
“…Eight papers from the primary literature (receiving 5 or more votes) were collectively identified as the most important by the author group. 11 -18 Results from the sorting process are depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight papers from the primary literature (receiving 5 or more votes) were collectively identified as the most important by the author group. 11 -18 Results from the sorting process are depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“… Flordelis Lasierra et al 14 Enteral nutrition in critically ill patients under vasoactive drug therapy: The NUTRIVAD study. …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the volatility of the patient's hemodynamic status and required dosage of the vasopressors, enteral feeding may be interrupted. 6,32 Another issue in evaluating feeding tolerance for patients who receive NMB is that many of the studies examining feeding intolerances and techniques designed to improve nutrient delivery often had a small number of patients from the total population (eg, <10%) who…”
Section: Interpreting the Relationship Between Nmb And Feeding Tolerancementioning
confidence: 99%
“…Reignier et al showed that AMI occurred more often in patients with shock receiving full enteral nutrition vs. full parenteral nutrition (PN) [51]. The more recent study applied enteral nutrition below estimated needs in patients with vasopressors and observed AMI in 1/200 patients (0.5%) [52]. Experimental data support caution toward (full) enteral nutrition in patients at risk of AMI, showing that preoperative fasting protected against intestinal ischemia/reperfusion injury and improved survival in mice [53 ▪▪ ].…”
Section: Specific Conditionsmentioning
confidence: 99%